Effects of support friction on mode I stress intensity factor and fracture toughness in SENB testing. (October 2019) - Ayatollahi, M.R.; Bahrami, B.; Mirzaei, A.M.; Yazid Yahya, M.
Highlights: Effect of support friction in SENB tests is assessed numerically and experimentally. Extensive FE analyses are performed to calculate SIF versus friction coefficient. Digital image correlation method is used to validate FE results. Values of fracture toughness extracted for different types of supports are compared. Neglecting effects of support friction generates significant errors in the extracted fracture toughness. Abstract: Effect of support friction on the values of stress intensity factor (SIF) and fracture toughness obtained from the single edge notch bending (SENB) specimen is evaluated both numerically and experimentally. In the first step, a comprehensive finite element (FE) study is performed to assess the friction effects for different dimensions of SENB specimen and various friction coefficients. The variations of stress intensity factor against the friction coefficient between the specimen and the bottom supports are evaluated. On the other hand, to investigate the friction effects experimentally, two different sizes of SENB specimens made of polymethyl methacrylate (PMMA) with three different types of contact between the supports and the specimens are considered. The digital image correlation (DIC) method is employed to assess the effect of support friction on the mode I SIF. Fracture tests are also performed on the PMMA specimens to obtain the critical stress intensity factor for each case separately. Both FE and experimental results reveal that the support friction affects the results significantly, and in order to extract the SIF and fracture toughness of PMMA accurately, it is mandatory to use the freely rotating roller contact between the supports and the SENB specimen.